2017
DOI: 10.1021/acsami.7b11055
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Gas Sensing of Two-Dimensional Titanium Carbide (MXene)

Abstract: Wearable gas sensors have received lots of attention for diagnostic and monitoring applications, and two-dimensional (2D) materials can provide a promising platform for fabricating gas sensors that can operate at room temperature. In the present study, the room temperature gas-sensing performance of TiCT nanosheets was investigated. 2D TiCT (MXene) sheets were synthesized by removal of Al atoms from TiAlC (MAX phases) and were integrated on flexible polyimide platforms with a simple solution casting method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
457
3
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 668 publications
(474 citation statements)
references
References 44 publications
11
457
3
3
Order By: Relevance
“…MXenes, as newly kind 2D materials, combine the rich surface terminations of function groups and high electrical conductivity, which indicates that they have the potential to make a great RT sensing material . Theoretical researches and experimental explorations in recent years have indeed proved this. Professor Cheng's studies, using first‐principle simulation, have shown that Ti 2 CO 2 and Ti 2 C 2 (OH) 2 could be excellent sensing materials for NH 3 gas molecules detection .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…MXenes, as newly kind 2D materials, combine the rich surface terminations of function groups and high electrical conductivity, which indicates that they have the potential to make a great RT sensing material . Theoretical researches and experimental explorations in recent years have indeed proved this. Professor Cheng's studies, using first‐principle simulation, have shown that Ti 2 CO 2 and Ti 2 C 2 (OH) 2 could be excellent sensing materials for NH 3 gas molecules detection .…”
Section: Introductionmentioning
confidence: 96%
“…As a kind of traditional sensing materials, metal oxide semiconductors can only work at high temperatures due to the presence of an activation energy . MXenes, as newly kind 2D materials, combine the rich surface terminations of function groups and high electrical conductivity, which indicates that they have the potential to make a great RT sensing material . Theoretical researches and experimental explorations in recent years have indeed proved this.…”
Section: Introductionmentioning
confidence: 98%
“…The outstanding properties of MXenes distinguish them from traditional 2D materials and make them promising candidates for energy storage and environmental applications, such as supercapacitors, lithium-ion batteries, and pollution treatment. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] The recent decomposition of 2D nanosheets into 0D nanodots has been used to develop materials for photocatalysis, sensors, and energy conversion owing to the unique confinement effect of 0D structures. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] The recent decomposition of 2D nanosheets into 0D nanodots has been used to develop materials for photocatalysis, sensors, and energy conversion owing to the unique confinement effect of 0D structures.…”
mentioning
confidence: 99%
“…In addition, the hydrophilic surface of MXene manifests the facile processing in aqueous environment without additional surfactant and surface modification, which facilitates the preparation of films and surface coatings. So far, MXenes have shown a wide variety of applications including the sensing, energy storage, catalysis, and photothermal conversion …”
Section: Introductionmentioning
confidence: 99%
“…[31,32] In addition, the hydrophilic surface of MXene manifests the facile processing in aqueous environment without additional surfactant and surface modification, which facilitates the preparation of films and surface coatings. So far, MXenes have shown a wide variety of applications including the sensing, [33][34][35] energy storage, [36] catalysis, [37,38] and photothermal conversion. [39][40][41][42] Olfactory sensing and perception play an important role in people's daily lives and greatly affects senses, emotions, and behavior.…”
mentioning
confidence: 99%